1995
DOI: 10.1063/1.468658
|View full text |Cite
|
Sign up to set email alerts
|

Direct Monte Carlo simulation of chemical reaction systems: Dissociation and recombination

Abstract: We report direct Monte Carlo simulations of a chemical reaction system with bimolecular and termolecular dissociation and recombination reactions of the type M ϩAB M ϩAϩB. The simulations are carried out at the molecular level using a simple flexible reaction model for termolecular reactions satisfying all the requirements of momentum and energy conservation, microscopic reversibility, and equilibrium. Energy transfer among reactants and products is included. The method is especially useful for treating reacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2000
2000
2005
2005

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…In fact, DSMC has become, de facto, the principal tool to investigate high Knudsen number flows. DSMC is also very useful for modeling flows involving chemical reactions [12][13][14][15]. DSMC is a direct particle simulation method based on the kinetic theory of gases.…”
Section: Dsmcmentioning
confidence: 99%
“…In fact, DSMC has become, de facto, the principal tool to investigate high Knudsen number flows. DSMC is also very useful for modeling flows involving chemical reactions [12][13][14][15]. DSMC is a direct particle simulation method based on the kinetic theory of gases.…”
Section: Dsmcmentioning
confidence: 99%
“…The results were found useful in understanding the expansion of high temperature uranium gas from a slit source [5]. Other systems examined thus far include homogeneous isotropic systems for an exothermic bimolecular reaction [6], a Lindemann-Christiansen reaction system [7], an energy-dependent unimolecular reaction [8], and a dissociation-recombination system [9]. In these studies we found the number of sample molecules required for adequate simulations to be far lower than we could have imagined.…”
Section: Introductionmentioning
confidence: 95%
“…the particle distribution f (r, v, t) is explicitly evaluated. It has been shown in [4,5] that the method can be used to study the details of gas phase chemical physical processes. This work has been generalized by our group by showing that realistic models of the vibrational kinetics of gas molecules can be included [6], and that even the quantum coherent kinetics of fast reactions can be included by addressing any particle with a local density matrix [7].…”
Section: Introductionmentioning
confidence: 99%